Automatic control design of light wall panel production line. Issue 1 (1st April 2022) - Chen, Jiwen; Meng, Decai; Zhang, Rui; Yang, Hongjuan; Bei, Taixue; Ji, Shuai
Abstract: In order to promote the intelligent and standardized production of green light-weight wall materials in prefabricated buildings, an electrical automation control system for light-weight wall panels based on PLC technology was proposed. The process flow of the wall panel production line is analyzed, and the hardware system of the control system is determined through the selection of hardware such as motors and cylinders. The batching system, extrusion molding system, cutting system, palletizing system, transfer and maintenance system, etc. can be programmed through PLC technology. and automated production of wall panels can be accomplished by utilizing sensors and limit switches.